2019
DOI: 10.1177/1532673x19875694
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Issue Messages and Voting Behavior

Abstract: In today’s data-driven campaigns, presidential targeting strategies rely on detailed perceptions about the political leanings and policy positions of Americans to decide which registered voters to contact and which messages to emphasize in their outreach. However, identifying supporters and opponents of a candidate’s policy positions is far from foolproof. This reality results in some citizens encountering political message(s) on congruent issues, where their issue stance aligns with the messaging candidate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…In sum, concordant with Endres (2019), we found that partisans can be negatively affected by a microtargeted message regarding their own candidate. In contrast with Endres (2019) and Matthes and Marquart (2015), we find that a message meant to be incongruent with the opinions of the receiver can have a significant and substantial negative attitudinal effect.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In sum, concordant with Endres (2019), we found that partisans can be negatively affected by a microtargeted message regarding their own candidate. In contrast with Endres (2019) and Matthes and Marquart (2015), we find that a message meant to be incongruent with the opinions of the receiver can have a significant and substantial negative attitudinal effect.…”
Section: Discussionsupporting
confidence: 83%
“…Evidence of how PMT amplifies effects on political behavior is scarce. Endres (2019: 1) found that targeting Democratic voters on issues on which they hold similar positions with the Republican candidate “is associated with decreased support” for the Democratic candidate, and “increased abstention, and increased support for” the Republican candidate. Haenschen and Jennings (2019) found that microtargeted online ads could increase turnout conditionally under Millennial voters: only in competitive districts.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…And, of course, election polling is further complicated by the reality that voters’ intentions and final decisions on whether or not to vote can change. Voters can even switch preferences at the last minute when they learn they disagree with a candidate on a wedge issue (Endres 2020; Endres and Panagopoulos 2019), like fracking, which Trump vigorously touted during visits to battleground states in the closing days of the campaign in 2020 (Grandoni 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Under certain conditions, PMTtechniques seem to mobilize young voters (Haenschen & Jennings, 2019). Moreover, targeting Democratic voters with a Republican issue-congruent message increases support for the Republican candidate (Endres, 2019). There is some literature on effects of opinion-congruity in a non-microtargeted political setting.…”
Section: Political Microtargeting and Personality Traitsmentioning
confidence: 99%